PROSES MEMBANGUN PEMAHAMAN KONSEPTUAL PADA SISWA KELAS IX PADA MATERI PERSAMAAN KUADRAT MTs AL ISLAHUDDINY KEDIRI - Musmiratul Uyun (JURNAL ILMIAH GLOBAL EDUCATION, 2020)
This study aims to describe the process of building conceptual understanding in grade IX students in mathematics at MTs Al-Islahuddiny Kediri. This type of research is a qualitative case study research. The research subjects were three XI grade students with high, medium and low academic abilities. The selection of research subjects was carried out by means of purposive sampling. The data of this research are in the form of data that students disclose regarding the process of building their conceptual understanding. The researcher took 2 observation data and 4 interview data from each research subject. The data analysis process was selected by examining all the data selected from the recording of the learning process and the results of the interviews. This study followed three stages of qualitative data analysis as outlined by Miles and Huberman, which included data reduction, data presentation, and conclusion drawing. This study reveals the process of building students' conceptual understanding of the quadratic equation material. Based on data analysis of three subjects in class XI MTs Al Islahuddiny Kediri, it shows that (1) Students with high academic abilities build conceptual understanding by reviewing the explanations that have been heard during the learning process in class, trying the examples given by the teacher and re-analyzing other questions is the way the first subject. In addition, the first subject always repeats the lesson with his roommate. (2) Students with academic abilities are building their conceptual understanding by relearning lessons learned at school and working on practice questions given by the teacher at school, When the second subject faced differences between the teacher's explanation at school and the material studied on student worksheets, the second subject marked the differences found and then asked his classmates the next day. (3) Students with low academic abilities build conceptual understanding by re-learning the lessons given by the teacher during the learning process in class, it is not uncommon for students to find difficulties when starting to do the exercises given by the teacher. This student asks the roommate about the completion process again when studying together before going to bed, After all the explanations were given by his friends, these students returned to doing the exercises independently and so on.